Possibilities of using Ukrainian companies’ open financial statements in the profitability analyzing of cash flows - Chaika, Tetiana; Poberezhna, Nataliia; Panasenko, Olga (Дике Поле, 2019)
Cash flow information is more transparent, easier to control, less affected by accounting policies, and more clearly shows whether a company generates real money. Therefore, it is obvious that when assessing the profitability, along with the other profitability ratios, it is also necessary to take into account return on cash flow ratios. The Ukrainian companies’ financial statements contain information that allows to calculate a number of cash flow profitability metrics. There are various approaches to the design of cash flow profitability metrics: some of them interpret cash flow as a dynamic form of company’s monetary resources, and others – as a result of financial activity. Cash flow profitability metrics are less susceptible to distortion than traditional profitability metrics calculated by profit. Unfortunately, the statistical reports of the Ukraine State Statistics Service do not contain information about the cash flows of the Ukrainian business entities, so there is no possibility to compare the obtained values with industry average indicators. This makes it difficult to carry out comparative analytical work when using metrics of cash flow profitability.

Інформація про рух грошових коштів більш прозора, легше піддається контролю, менше схильна до впливу облікової політики та чіткіше показує, чи генерує компанія реальні грошові кошти. Тому очевидно, що при оцінці прибутковості підприємства, поряд з іншими коефіцієнтами рентабельності, необхідно брати до уваги також і коефіцієнти рентабельності грошових потоків. Фінансова звітність українських підприємств містить інформацію, яка дозволяє розрахувати цілий ряд метрик рентабельності грошового потоку. Існують різні підходи до конструювання метрик рентабельності грошового потоку: одні з них трактують грошовий потік як динамічну форму грошових ресурсів підприємства, а інші – як результат фінансової діяльності. Метрики рентабельності грошового потоку менш схильні до спотворень, ніж традиційні метрики рентабельності, які розраховані за прибутком. На жаль, статистичні звіти Державної служби статистики України не містять інформації про грошові потоки українських суб'єктів господарської діяльності, тому відсутня можливість порівнювати отримані значення з середньогалузевими показниками. Це істотно ускладнює проведення порівняльної аналітичної роботи при використанні метрик рентабельності грошових потоків.
Можливості використання відкритої фінансової звітності українських підприємств при аналізі рентабельності грошових потоків
Keywords: cash flow; profitability analyzing; financial statements; Return on Positive Cash Flow; Return on Net Cash Flow; Return on Average Cash Balance; Return on Net Operating Cash Flow; Return on Net Investment Cash Flow; Return on Net Financial Cash Flow; грошовий потік; рентабельність грошових потоків; фінансова звітність; рентабельність позитивного грошового потоку; рентабельність чистого грошового потоку; середній залишок грошових коштів; операційна діяльність; інвестиційна діяльність; фінансова діяльність